Comparison Of Engine Performance For Different Type Of Engines With Alternative Fuels During Complete Flight Trajectory - Halim, Aiqa Arbila Abdul (Universiti Sains Malaysia, 2019)
Airline industry has experienced a huge amount of improvements in fuel efficiency and this is due to the increasing harmful effects caused by them. One of the contributing approaches is using alternative fuels which are plant-based, and it wasn’t in vain as there have been three successful biofuel flights which are Air New Zealand’s Boeing 747-400, Continental Airlines Boeing 737-800 and Japan Airline Boeing 747-300. Thus, this study is conducted to compare and analyze the engine performance (thrust, specific fuel capacity, and mass fuel flow) of different type of engines (single-spool and double-spool engine) operating with alternative fuels (Jet- A, JSPK, CSPK, mixture of 50% JSPK + 50% Jet-A, mixture of 50% CSPK + 50% Jet-A, Palm Methyl Ester, Canola and Halophyte) during complete flight trajectory (take-off, top of climb, cruise, low power and ground idle). The engines are modelled, and the simulation is performed using the Gas Simulation Program software. This research analyzes the effect of alternating fuels on the engine performance during a complete flight trajectory. The results show that the best alternative fuel that could replace the conventional Jet-A is JSPK. It has the capability to produce similar and better engine performance in terms of thrust, lower specific fuel consumption and a reduction of mass fuel flow. JSPK blend, CSPK and CSPK blend fuels can also produce similar engine performance and used as alternative fuels. However, POME, POME blend, Canola and Halophyte are not able to produce similar or better engine performance compared to Jet-A fuel hence is not a suitable choice to replace the conventional Jet-A. This thesis draws the conclusion on the possibility of incorporating alternating fuels for GHC effects prevention.